Synthesis and semiconducting studies of 2-Hydroxyacetophenone-formaldehyde-melamine copolymers - Gupta, R H; Gurnule, W B (Recent Research in Science and Technology, 2012)
Copolymers were synthesized by condensation of 2-hydroxyacetophenone (2-HA) and melamine (M) with formaldehyde (F) in the presence of 2 M HCl as catalyst with varied molar ratios of reacting monomers. The electrical properties of 2-HAFM-I, 2-HAFM -II, 2-HAFM -III and 2-HAFM -IV copolymers were measured over a wide range of temperature (303-423 K). From the electrical conductivity of these copolymers, activation energies of electrical conduction have been evaluated and values lies in the range 7.38 x 10-20 – 6.52 x 10-20 J/K. The plots of log σ vs 103/T are found to be linear over a wide range of temperature, which indicate that the Wilson’s exponential law σ = σ0 exp(-ΔE/kT) is obeyed. On the basis of above studies, these copolymers can be ranked as semiconductors.